Identification and investigation of antibiotic resistance patterns of pathogenic bacteria isolated from Iloilo River. - Salvoza, Noel Calumno (2010.)
The prevalence of antibiotic resistance among various bacterial species often resulted from teh increase and often indiscriminate use of antibiotics from medical, agricultural, and veterinary practices. Antibiotics, along with antibiotic-resistant bacteria excreted fromt he human and animal body will eventually find their way into water-table and ultimately into streams and rivers. Thus, this study investigates the antibiotic susceptibility of isolated pathogenic bacteria from Iloilo River. The four pathogenic bacteria E. coli, Salmonella spp., Vibrio spp., and Streptococcus spp. were isolated from water and sediment samples collected from the five sampling points of the Iloilo river. A total of 1183 isolates were obtained: 70 for E.coli; 90 for Salmonella spp.; 370 for Vibrio spp.; and 542 for Streptococcus spp. Fifty samples of each species were randomly selected and tested for antimicrobial susceptibility to different antibiotics representing each class. Results show that majority of the isolates were susceptible to chloramphenicol (22 percent), erythromycin (28 percent), ciprofloxacin (28 percent) and gentamicin (35 percent). Among all the isolates tested, E. coli and Vibrio spp. isolates were themost resistant. The highest frequency of resistance were observed in oxacillin (97 percent of the islates), followed by penicillin (96 percent). majority of the isolates showed multiple resistance to several antibiotics. Most of the isolates were resistant to 4-6 antibiotics used in this study. Decreasing ARI trend for Salmonella spp. and E. coli from Sooc to Forbes was established. These findings imply that the condition of Iloilo River is no longer safe for human activities. The level of antibiotic resistance in the river presents a potential public health risk, as well as the risk of transferring the antibiotic resistance to bacterial populations in the environment.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Iloilo River